ИНТЕРАКТИВНЫЕ МЕТОДЫ И ПРИЁМЫ НА УРОКАХ РУССКОГО ЯЗЫКА КАК ЭФФЕКТИВНЫЙ МЕТОД ОБУЧЕНИЯ - Худойбердиева Муаззам Зайнобидиновна (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2023)
Annotation: This article addresses topical issues on the use of interactive teaching methods in the lessons of Russian as a foreign language. The main task of modern school education is not only the accumulation by the student of a certain amount of knowledge, skills, abilities, but also the preparation of the student as an independent subject of educational activity.